Perspektif Ulama Perempuan Sasak terhadap Relasi Gender dalam Perkawinan Sasak - Jumarim Jumarim (FONDATIA, 2022)
This study aims to describe and identify the form of gender relations in the practice of Sasak marriage and to describe and map the perceptions of female clerics about equal and fair gender relations. The subjects of this research are female Sasak clerics who have expertise in the field of religious knowledge, have social roles, and become administrators or leaders of Islamic community organizations. The main source of data in this study is the perception of female Sasak clerics who are oral, written and action, both those that have been documented by themselves or other parties or those that have not been then drawn conclusions using inductive-deductive techniques. The results of the study show unequal gender roles, ranging from arbitration, authenticity and selabaran, pisuke, marriage contracts (ijab-qabul, witnesses, dowries, marriage sermons), penghulu, marriage certificates and sorong-sarah-ajikrame. Even though the female Sasak clerics understand that in theory of gender justice, there are indeed many positions of women as parties that are not equal to men in terms of Sasak marriage customs and Islamic Marriage Law. However, for those who have never carried out the Sasak marriage custom and those who have lived it, they are of the view that the thing that must be achieved by marriage is its goal, namely to become a sakinah, mawaddah wa rahmah family, which will be felt by those who hold a marriage, namely husband and wife. his extended family and of course his descendants. Households formed through the institution of marriage (both using adat and fiqh and Islamic law) will become educational institutions that continuously strive to provide understanding, knowledge, experience and skills that will mature their managers (husband and wife) as well as their offspring as students.